TECHNOLOGY ADOPTION IN THELITERATURE FROM 2020 TO 2024 - Julio E Crespo (IPHO-Journal of Advance Research in Science And Engineering, 2024)
The pandemic was mitigated and controlled through distancing and confinement policies, but the stigma towards anti-COVID-19 devices opened the discussion about trust and adoption towards preventive technology. The aim of this paper was to explore the dimensions of trust and adoption of anti pandemic technology. A cross-sectional, psychometric and correlational study was carried out with a sample of 186 students selected for the use of anti-COVID-19 technology in their professional practices and social service.The results show three dimensions related to the usefulness, efficiency and use of anti-pandemic technology.In relation to the state of the art, the scope and limits of the study are highlighted in order to propose the extension of the model.